The Relationship Between Entrepreneurship Learning and Entrepreneurial Creativity in Vocational School Students in Jombang Regency: The Role of Social Support as A Mediating Variable - Alimaningtyas, Deni; Wardana, Ludi Wishnu; Sumanto, Agus (Journal of Applied Business, Taxation and Economics Research, 2025)
Entrepreneurship plays an important role in solving complex problems such as poverty, inequality and economic instability. Young people equipped with entrepreneurial skills are not only drivers of economic growth, but also agents of change who can address the major challenges faced by society and the global environment. The importance of creativity in this context is because innovation is a key driver in business and technological development. Creativity allows new ideas to emerge, provides more effective and efficient solutions, and creates significant added value for society. This research uses a quantitative approach with Partial Least Squares structural equation modeling (PLS-SEM) to predict and confirm the given hypothesis. This research uses google form for data collection on grade XI students in the Digital Business Department of SMKN in Jombang Regency. Respondents in this study were 136 respondents from the three schools used as research objects. The results of the research analysis show that social support has a significant influence on entrepreneurial creativity, showing a strong and positive relationship. Entrepreneurship learning also has a significant effect in increasing social support. However, the direct relationship between entrepreneurial learning and entrepreneurial creativity is negative and insignificant. Thus, social support plays an important role as a mediator in enhancing entrepreneurial creativity.